Social Interaction and Identity Construction Among Adolescents in Social Psychology - Seul, Harry; Yusbar, Yusbar; Lumaga, Joni (Journal Social Humanity Perspective, 2025)
This paper addresses social interaction and identity formation in adolescents based on the concept of social psychology, especially in its implication to the study of management. The study is based on a qualitative approach, and investigates the role of peers, family and online spaces as the place where teenagers are negotiating belonging, validation and self-presentation. Results indicate that peer interaction offers the relevant feedback loops that either confirm or question the new identities of adolescents, whereas families are both a source of stabilizing anchor and an antagonistic stage where intergenerational expectations are negotiated. Digital platforms also go even further in broadening the field of identity work, providing space to experiment and perform, but also putting additional pressures on social comparison and validation. Combined, these processes show that identity construction is not limited to individual growth but is a larger organizational phenomenon and reverberates the relations of recognition, negotiation and accommodation within institutions. The paper presents an argument according to which the concept of identity as a dynamic capability developed during adolescence can be of help to management practices in leadership, human resource management and organizational culture. Environments that contribute to inclusivity, resilience, and performance can be provided by institutions that acknowledge and endorse identity-sensitive processes. The results help in closing the gap between social psychology and management literature, in the development of a paradigm in which initial social experiences are recognized as antecedents of subsequent organizational decision-making and institutional engagement.